Pengaruh Nilai Tukar Rupiah dan Suku Bunga Terhadap Indeks Harga Saham Gabungan Periode Tahun 2023-2024 - Sri Bulkia; Orbawati Orbawati; Husnurrofiq Husnurrofiq; Sanusi Sanusi (Pusat Riset dan Inovasi Nasional, 2026)
Changes in the value of financial exchange have significant implications that have multi-faceted consequences. Secondly, these fluctuations directly influence the competition of domestic Jaisai products on the global stage. When the value of local foreign exchange increases, export products can become more expensive in international markets, while imported products become more affordable, so their income can affect the financial performance of companies listed in Bursai Indonesia Effect. Secondly, changing the value of exchange is also crucial in determining the capital and investment in stock market. As a result, the weakening value of the rupiah exchange rate can reduce the potential profits for foreign investors who want to increase capital, because the value of their investments will decrease. This condition often results in a general decline in investors' interest in capital, resulting in a negative impact on the Composite Stock Price Index. Interest rate variables and exchange rates are comparable and have a significant impact on the Composite Stock Price Index. This is proven by the scientific significance value which reaches 0.001, which is lower than the scientific significance value determined by (0.05). The findings of this F test show that H0 is rejected and H1 is accepted.